Hubungan Pola Asuh Orang Tua Dengan Masalah Perilaku Dan Emosional Pada Anak Di SDN Kandang Cut Kabupaten Aceh Besar - Firda Jasrin; Cut Oktaviyana; Dewi Sartika; Muhammad Iqbal S (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Behavioral and emotional problems are very influential on the mental development and growth of children. Parenting is a pattern of behavior that is applied to children over time. Authoritarian parenting with behavior, permissive parenting with behavior, and democratic parenting with behavior. Authoritarian parenting with emotions, permissive parenting with emotions, and democratic parenting with emotions. The purpose of this study was to determine the relationship between parenting patterns toward behavioral and emotional problems in children. This research design was a correlation description with a cross-sectional approach. The population was parents in SDN Kandang Cut, Aceh Besar, totaling 78 respondents, using a total sampling technique on January 16-17, 2023. The results show that most of the respondents positively applied parenting actions, as many as 42 respondents (53.8%). The results also indicate that there was a relationship between parenting patterns and children’s behavior, p-value = 0.007, there was a relationship between parenting patterns and children’s emotions, p-value = 0.017, there was a relationship between authoritarian parenting patterns and children’s behavior p-value = 0.047, there is a relationship between permissive parenting and children’s behavior, p-value = 0.008, there is no relationship between democratic parenting and children’s behavior, p-value = 0.077, there is a relationship between authoritarian parenting and children’s emotional p-value = 0.047, there is a relationship between permissive parenting and children’s behavior, p-value = 0.008, there is no relationship between democratic parenting and children’s behavior, p-value = 0.077, there is a relationship between authoritarian parenting and children’s emotional p-value = 0.015. However, this study also reveals that there is no relationship between permissive parenting patterns and children’s emotionality, p-value = 0.736, and there is no relationship between democratic parenting patterns and children’s emotionality in SDN Kandang Cut with p-value = 0.189. It is expected that parents should increase their knowledge by exploring information about parenting patterns, behavior, and also children's emotions.